2022
DOI: 10.1093/cid/ciac262
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Naturally Acquired Immunity versus Vaccine-induced Immunity, Reinfections versus Breakthrough Infections: A Retrospective Cohort Study

Abstract: Background Waning of protection against infection with SARS-CoV-2 conferred by 2 doses of the BNT162b2 vaccine begins shortly after inoculation and becomes substantial within four months. With that, the impact of prior infection on incident SARS-CoV-2 reinfection is unclear. Therefore, we examined the long-term protection of naturally acquired immunity (protection conferred by previous infection) compared to vaccine-induced immunity. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
81
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 15 publications
11
81
2
1
Order By: Relevance
“…Compared to prior studies, 8,2628 our estimates for protection against reinfection were substantially lower than those analyzing infections during pre-Omicron outbreaks; furthermore, we found significant differences in protection conveyed by prior infections before and during the emergence of the Delta variant. Consistent with other studies 11,14 , we found the highest levels of protection among those who had three doses of vaccination and prior infections.…”
Section: Discussioncontrasting
confidence: 92%
“…Compared to prior studies, 8,2628 our estimates for protection against reinfection were substantially lower than those analyzing infections during pre-Omicron outbreaks; furthermore, we found significant differences in protection conveyed by prior infections before and during the emergence of the Delta variant. Consistent with other studies 11,14 , we found the highest levels of protection among those who had three doses of vaccination and prior infections.…”
Section: Discussioncontrasting
confidence: 92%
“…For our primary analysis, cases were matched to controls using 1:m matching, with up to five controls per case, based on seven factors: sex, age group (using a binary cut-off age of ≥70 years, because studies 19 have indicated that older age groups are at higher risk, especially for severe disease), city of residence, socioeconomic status, calendar week of first test (to account for potential time-varying risk within the outcome period), the month of receipt of the third dose (to mitigate possible bias related to waning of the third dose), and a categorical variable for the living environment (a medical nursing home, an assisted living facility, or a private residence). The last factor was included because of early pandemic increases in SARS-CoV-2 infection in nursing homes and assisted living facilities, which led to differential regulations in these institutions, mandating staff and residents to be vaccinated and limiting visits from non-residents.…”
Section: Methodsmentioning
confidence: 99%
“…Vaccine passports risk enshrining discrimination based on perceived health status into law, undermining many rights of healthy individuals: indeed, unvaccinated but previously infected people may generally be at less risk of infection (and severe outcomes) than doubly vaccinated but infection-naïve individuals 80. A weekly negative SARS-CoV-2 test is often seen as a compromise in lieu of full vaccination status, but this places additional burdens (including financial) on the unvaccinated while also risking reputational damage.…”
Section: The Political and Legal Effects Of Vaccine Mandates Passport...mentioning
confidence: 99%
“…It would violate the proportionality principle to impose significant liberty restrictions (and/or harms) in exchange for trivial public health benefits, particularly when other options are available. Evidence shows that the efficacy of current COVID-19 vaccines on reducing transmission is limited and temporary,7–16 likely lower in younger age groups targeted for vaccine mandates and passports36 and that prior infection provides, roughly speaking, comparable benefit 18 31 80. The effectiveness of vaccine mandates in reducing transmission is likely to be smaller than many might have expected or have hoped for, and decrease over time.…”
Section: The Integrity Of Science and Public Healthmentioning
confidence: 99%